A Systematic Review and Recommendations Around Frameworks for Evaluating Scientific Validity in Nutritional Genomics - Keathley, Justine; Garneau, Véronique; Zavala-Mora, Daniela; Heister, Robyn R.; Gauthier, Ellie; Morin-Bernier, Josiane; Green, Robert; Vohl, Marie-Claude (Frontiers in Nutrition, 2021)
There is a significant lack of consistency used to determine the scientific validity of nutrigenetic research. The aims of this study were to examine existing frameworks used for determining scientific validity in nutrition and/or genetics and to determine which framework would be most accurate to evaluate scientific validity in nutrigenetics in the future. A systematic review (PROSPERO registration: CRD42021261948) was conducted up until July 2021 using Medline, Embase and Web of Science, with articles screened in duplicate. Grey literature searches were also conducted (June-July 2021), and reference lists of two relevant review articles were screened. Included articles provided the complete methods for a framework that has been used to evaluate scientific validity in nutrition and/or genetics. Articles were excluded if they provided a framework for evaluating health services/systems more broadly. Citing articles of the included articles were then screened in Google Scholar to determine if the framework had been used in nutrition or genetics, or both; frameworks that had not were excluded. Summary tables were piloted in duplicate and revised accordingly prior to synthesizing all included articles. Frameworks were critically appraised for their applicability to nutrigenetic scientific validity assessment using a predetermined categorization matrix, which included key factors deemed important by an expert panel for assessing scientific validity in nutrigenetics. Upon screening 3931 articles, a total of 49 articles representing 41 total frameworks, were included in the final analysis (19 used in genetics, 9 used in nutrition and 13 used in both). Factors deemed important for evaluating nutrigenetic evidence related to study design and quality, generalizability, directness, consistency, precision, confounding, effect size, biological plausibility, publication/funding bias, allele and nutrient dose-response, and summary levels of evidence. Frameworks varied in the components of their scientific validity assessment, with most assessing study quality. Consideration of biological plausibility was more common in frameworks used in genetics. Dose-response effects were rarely considered. One included framework incorporated all but one predetermined key factor important for nutrigenetic scientific validity assessment. A single existing framework was highlighted as optimal for the rigorous evaluation of scientific validity in nutritional genomics, and minor modifications are proposed to strengthen it further.